Burnout and health status differences among primary healthcare professionals in Portugal - Ferreira, Pedro L. (2021)
This paper is focused on two indicators which may be considered as proxies of individuals' well-being: self-assessed health and burnout intensity. There is little research relating these concepts with the type of the primary healthcare setting, its urbanization density and the region. The aims of this work are threefold: (i) to find determinant factors of individual health status and burnout, (ii) to find possible differences across different types of health care units, differently urbanized areas, and different administrative regions, and (iii) to verify if there are differences in between GPs and nurses. Methods: Data was gathered from an online questionnaire implemented on primary health care. A sample of 9,094 professionals from all 1,212 primary health care settings in Portugal mainland was obtained from an online questionnaire filled from January and April 2018. Statistical analyses include the estimation of two ordered probits, one explaining self-assessed health and the other the burnout. Results: The individual drivers for good health and lower levels of burnout, that is, better well-being, are estimated for GPs and nurses. Main findings support that, first, nurses report worst health than GPs, but the latter tend to suffer higher levels of burnout, and also that, ’place’ effects arising from the health unit settings and regional location are more significant in GPs than in nurses. However, urbanization density is not significantly associated with health or burnout. Conclusions: A set of policy recommendations are suggested to improve the healthcare workforce well-being, such as improving job satisfaction and income. These policies should be taken at the health care unit level and at the regional administrative level.